PENGARUH CORPORATE SOCIAL RESPONSIBILITY TERHADAP NILAI PERUSAHAAN DENGAN PROFITABILITAS SEBAGAI VARIABEL MODERATING - Suharno, Ihwan Sunaryo, Bambang Widarno & (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2018)
The purpose of this study is to: 1) Analyze the significance effect of corporate social responsibility on firm value 2) Analyze the significance effect of profitability on firm value and 3) Analyze the effect of corporate social responsibility on firm value with profitability are moderated. This type of research is an empirical study. The research population is a manufacturing company of the pharmaceutical sub-sector listed on Indonesia Stock Exchange Year 2013 – 2016. Samples of 8 companies with purposive sampling technique. The data source uses secondary data. Data collection techniques used documentation. Data analysis techniques use multiple linear regression and absolute difference test. The results showed that corporate social responsibility has a positive and significant effect on firm value. Profitability has a positive and significant effect on firm value. Profitability moderates the effect of corporate social responsibility on firm value.Keywords: corporate social responsibility, profitability, firm value